Analysis of risk factors for uterine atonia prolonged part, anemia, age and parity: A literature review - Rini Gustina Sari; Anisa Safitri; Texi Monica; Khetrin Patra (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Uterine atony is defined as the leading cause of postpartum hemorrhage, which is the largest contributor to maternal mortality. Numerous studies have shown that factors such as prolonged labor, anemia during pregnancy, maternal age, and parity are associated with the incidence of uterine atony Purpose: to analyze and synthesize findings from five journals related to these risk factors. Method: The method used was a literature review of journals with a cross-sectional and case-control approach, with a total sampling technique and chi-square and Fisher correlation tests. Results: The results show that prolonged labor increases uterine muscle fatigue, resulting in decreased contractions. . Anemia causes reduced oxygen supply to uterine tissue, which impacts contraction failure. Maternal age under 20 and over 35 increases the risk due to unpreparedness and decreased organ function. High parity also contributes to decreased elasticity and strength of uterine contractions. Conclusion: The conclusion of this review indicates that all of these factors are significantly associated with the incidence of uterine atony, so preventive efforts through early detection and improving the quality of antenatal care are needed.